Fefferman-Stein decomposition for Q-spaces and micro-local quantities. (November 2016) - Yang, Qixiang; Qian, Tao; Li, Pengtao
Abstract: In this paper, we study the Fefferman-Stein decomposition of Q α ( R n ) and give an affirmative answer to an open problem posed by Essén et al. (2000). One of our main methods is to characterize the structure of the predual of Q α ( R n ) by the micro-local quantities. This result indicates that the norm of the predual space of Q α ( R n ) depends on the micro-local structure in a self-correlation way.